THE VIEW OF CONSUMERS TO RETAIL BRANDS; AN EXAMPLE OF A COOPERATIVE BRAND (Third Sector Social Economic Review, 2017)
Retail brands,  named and created specifically by the retailer, could be used for a variety of product range. On the other hand, cooperative brands, the institutions having shared economic, social and cultural needs and wants, usually operates in a more specific product range. It will be necessary for retail brands that assess prospectively the usage of a brand in a broad scope and developing cooperative brands to know which products consumers purchase, what decision processes they make and about which factors affect these processes and to take their strategic moves according to these processes. In today’s time, where ideas and information spread quickly, consumers’ perceptions of brands are affected by a plenty of factors. Identifying these factors correctly will guide the brands to take their  steps in the right direction and reveal the information related to appropriate positioning criteria. In the decision process of brand strategies the interpreting consumer behaviors will gain great prominence.
Keywords: Retail Brand; Cooperative Brand; Private Label; Collective Brand